A New Direction of Islamic Education in Indonesia: Opportunities and Challenges in the Industrial Revolution Era 4.0 - Akrim Akrim (Edukasi Islami: Jurnal Pendidikan Islam, 2022)
This article aims to discuss the dynamics of development and discourse of Islamic education in studying with a futuristic approach, how the challenges and opportunities of Islamic education in the Revolutionary Era 4.0 are commonly referred to as the Era of Disruption. The method used is qualitative research method with library approach, the primary source used is literature, journals, and books related to the topic discussed. The discussion results showed various forms of opportunities and challenges faced by Islamic education in Indonesia, especially in the era of disruption, whose signs begin with globalization. Despite many options, Islamic education should also be wary of challenges. This study found various challenges, namely the ability of Islamic education to harmonize divine verses with kauniyah verses, maintaining the process of Islamization of science. Harmonize the God-human relationship in the form of a the-anthropo-centric education with the point of the press; man is a noble being of God. Harmonizing between faith and knowledge cannot be separated. He is adjusting between the fulfillment of spiritual needs (spiritual-ukhrowi) and the realization of physical (material-earthly) needs and harmonizing between revelation and intellect (thinking, critical and rational).